A comparison of pathological findings in head computed to-mography with clinical presentation of pediatric patients in the Emergency Department - Lipiński, Łukasz; Lipińska, Justyna; Kopeć, Izabela; Kowalczuk, Maria; Woźniak, Magdalena (Journal of Education, Health and Sport, 2023)
Pediatric trauma is a cause for over 750.000 visits to emergency departments each year. Of all types of traumas, head injuries represent the group at most risk. Computed tomography (CT) is still the most frequently used advanced imaging method to distinguish cases of severe injuries out of thousands of mild or apparently trivial injuries. The aim of this study was to review the results of CT in terms of clinical prediagnosis and radiological findings in children categorized into four age groups, who underwent a CT scan in the Pediatric Emergency Department (ED). Among all CT studies, no findings were found in 552 (80.23%) patients, whereas CT findings were detected in 98 (14.2%) boys and 38 (5.5%) girls from all participants. The incidence of lesions in the male group is 2 times higher than in the female group. The most common abnormality was hematoma representing 26.47% of all confirmed lesions and 5.23% among all head CTs performed from the ED. Head CT is an incredibly useful tool in the evaluation of some head emergencies. However, in the majority of cases, the clinical presentation with which children present to the ED does not correlate with the severity of neuroimaging results.